The Role of Atrial Premature Complexes in Exercise Test in Predicting Atrial Fibrillation in Patients Without Obstructive Coronary Artery Disease. - Tezen, Ozan; Pay, Levent; Yumurtaş, Ahmet Çağdaş; Çetin, Tuğba; Eren, Semih; Öz, Melih; Coşkun, Cahit; Karabacak, Cemre; Yenitürk, Birkan; Çınar, Tufan; Hayıroğlu, Mert İlker (Pacing & Clinical Electrophysiology, 2024)
Background: Atrial fibrillation (AF) is usually triggered by frequent atrial premature complexes (APC) and atrial tachycardias originated in the pulmonary veins. The aim of the current study is to clarify the relationship between AF and APCs observed during treadmill exercise testing through long‐term patient follow‐up. Material and Methods: Our study only examined the data of patients who did not have any obstructive coronary artery disease and had an exercise test. In total, 1559 patients were included in this research. The study data were divided into two groups according to the development of AF during follow‐up. The patients who developed any type of AF during the follow‐up period were classified as AF (+). Mean follow‐up time for AF (+) and (−) groups were 48 and 47 months, respectively. Results: In the univariable analysis, age, LAAP, and the presence of APCs (HR: 3.906, 95% CI: 2.848–5.365, p < 0.001) during the treadmill exercise test were significantly associated with the development of AF. In the multivariable analysis, age (adjusted HR: 1.063, 95% CI: 1.043–1.083, p < 0.001) and the presence of APCs during the treadmill exercise test (adjusted HR: 2.504, 95% CI: 1.759–3.565, p < 0.001) emerged as independent risk factors for the development of AF. The AF‐free survival was significantly lower in the APCs (+) patients compared with the APCs (−) patients (log rank p < 0.001). Conclusion: Our study revealed that individuals without obstructive CAD who exhibited frequent APCs during treadmill exercise tests were more likely to develop AF.